Absolvo te! Komizm w pierwszych rosyjskich utworach fantastycznych - Cudowski, Tomasz (Przegląd Środkowo-Wschodni, 2022)
The article analyzes the first stories of modern Russian fantastic literature in terms of its comic motifs. The sources and forms of comicality are identified, as well as their meaning and the reasons why the authors who laid the foundations for Russian fantastic genre used comic elements at the turn of the 18th and 19th centuries. The first authors of the Russian fantastic literature, such as Nikolai Karamzin, Alexandr Bestuzhev-Marlinsky, Antony Pogorelsky or Orest Somov, were strongly influenced by pre-romantic trends, for which comism was a completely strange category, contrary to their nature. However a bit later, more popular Russian fantastic writers, such as Nikolai Gogol, Alexandr Pushkin, Ivan Turgenev and Fyodor Dostoyevsky, creators of the fantastic literature of that period, did not avoid comic elements in their works.